Pengaruh Mekanisme Good Corporate Governance, Debt to Equity Ratio, Asset Growth terhadap Kinerja Perusahaan - Kartika Mirawati Tika Mirawati; Meina Wulansari (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2018)
This study aims to determine the effect of the mechanism of Good Corporate Governance, DER, Asset Growth on company performance (empirical studies on mining companies listed on the Indonesia, Thailand, Malaysia Stock Exchange period 2010-2017). This research is a quantitative research which aims to systematically explained about the facts and properties in an object in the study then merged between variables related to it by presenting secondary data from financial reports from mining companies in the countries of Indonesia, Malaysia and Thailand. The population used in this study were mining companies listed on the Indonesia, Malaysia and Thailand Stock Exchanges in the period 2013 to 2017. The samples used in this study were 15 mining companies in the countries of Indonesia, Malaysia and Thailand by using the Purpose Method. Sampling the objectives for obtaining a representative sample that matches the criteria that have been confirmed. In this study, the data analysis method used is the data panel (pooled data) which is a combination of time series data and data between individuals or cross sections in mining companies in Indonesia, Malaysia and Thailand. Research Results for mining companies in Indonesia The R square value of this model is 0.732 percent, meaning that the variation of the profit company's performance can be explained by the independent variables analyzed, namely the mechanism of Good Corporate Governance, DER, the remaining Asset Growth percent of 73.20 the remaining 26.80 percent is explained by other factors not included in this study. Furthermore, the R square value of this model of 0.731 percent means that the variation of the company's profit performance can be explained by the independent variables analyzed, namely the mechanism of Good Corporate Governance, DER, the remaining percent Asset Growth of 73.10 the remaining 26.90 percent is explained by other factors not included in this research .. and thailand country The R square value of this model is 0.849 percent which means that the variation of profit that can be explained by the independent variables analyzed are NIM, BOPO, CAR and NPL of 84.90 percent of the remaining 15.10 percent is explained by other factors that do not included in this study.